Climate Change Integration in the Multilevel Governance of Italy and Austria Shaping Subnational Policies in the Transport, Energy, and Spatial Planning Sectors - Federica, Cittadino; Parks, Louisa; Bußjäger, Peter; Rosignoli, Francesca (Brill, 2022)
How can subnational governments best integrate climate change considerations across policy areas? Which factors contribute to successful integration? With a specific focus on transport, spatial planning policies, and energy and water in selected cases located at the border of the Alpine region between Italy and Austria, this volume shows that coordination (vertical and horizontal), public participation and information, leadership, and dedicated funding play fundamental and interlinked roles in climate change policy integration.